The Effect of the Educational Plaything Number Puzzle on Fine Motor Improvement of Preschooler Aged 4-6 Year - Ni Nyoman Murti; Ega Ersya Urnia (Humanistic Network for Science and Technology (HNST), 2018)
UNICEF data in 2011 showed a high rate in growth and developmental disorders in children; especially, motor development disorders of 27.5%. In other words, 3 million children experience it. Based on national data from the Ministry of Health of the Republic of Indonesia, in 2010, 11.5% of children in Indonesia experienced growth and developmental disorders. This research aimed to determine the effect of educational plaything ‘number puzzle’ on the improvement of fine motor skills of preschoolers aged 4-6 years. This was quasi-experimental research with a non-equivalent control group design. Based on the results of statistics tests using the MannWhitney test, the p-value = 0.013 for fine motor difference between experimental and control groups and the pvalue 0.018 for improvement in fine motor development in the experimental group. There was a significant effect on the provision of stimulus in the form of an educational plaything ‘number puzzle in improving the fine motoric of preschoolers aged 4-6 years. Keywords: educational plaything, fine motor